2006
DOI: 10.2345/i0899-8205-40-3-233.1
|View full text |Cite
|
Sign up to set email alerts
|

Medical Equipment Management Strategies

Abstract: Clinical engineering professionals need to continually review and improve their management strategies in order to keep up with improvements in equipment technology, as well as with increasing expectations of health care organizations. In the last 20 years, management strategies have evolved from the initial obsession with electrical safety to flexible criteria that fit the individual institution's needs. Few hospitals, however, are taking full advantage of the paradigm shift offered by the evolution of Joint C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 3 publications
0
31
0
3
Order By: Relevance
“…criticality to the organization's mission: the likelihood and severity of the impact of an equipment failure on the hospital's mission of providing care to patients, including the effects of delayed and/or interrupted diagnostics and therapeutics, and also the consequential impacts on patient satisfaction and institutional finances [Wang et al, 2006a]. criticality to the organization's mission: the likelihood and severity of the impact of an equipment failure on the hospital's mission of providing care to patients, including the effects of delayed and/or interrupted diagnostics and therapeutics, and also the consequential impacts on patient satisfaction and institutional finances [Wang et al, 2006a].…”
Section: Maintenance Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…criticality to the organization's mission: the likelihood and severity of the impact of an equipment failure on the hospital's mission of providing care to patients, including the effects of delayed and/or interrupted diagnostics and therapeutics, and also the consequential impacts on patient satisfaction and institutional finances [Wang et al, 2006a]. criticality to the organization's mission: the likelihood and severity of the impact of an equipment failure on the hospital's mission of providing care to patients, including the effects of delayed and/or interrupted diagnostics and therapeutics, and also the consequential impacts on patient satisfaction and institutional finances [Wang et al, 2006a].…”
Section: Maintenance Planningmentioning
confidence: 99%
“…2000; Wang et al, 2006a;ECRI, 2012]. As a full description and discussion of this subject would require too much space, readers are referred to Wang [2008] for an in-depth treatment.…”
Section: Maintenance Planningmentioning
confidence: 99%
“…When such data become available, it will be possible to use them to review maintenance planning models that consider mission criticality. 18,19 …”
Section: Revision and Improvement Of Maintenance Planningmentioning
confidence: 98%
“…Unfortunately this is a time-and cost-intensive approach. Another approach suggests focusing on the risk posed by equipment failure on larger groups of patients, rather than focusing on the equipment with the highest maintenance demand [4]. Some authors have suggested categorizing systems according to their level of complexity as a guide for system management, optimization, and cost reduction, [5] as well as proposing a rule base for real-time equipment replacement prioritization [6].…”
Section: Introductionmentioning
confidence: 99%